2015
DOI: 10.11648/j.ejpm.20150303.14
|View full text |Cite
|
Sign up to set email alerts
|

Young Women Sexual Behaviour and Self-Reported Sexually Transmitted Diseases in Northern Ethiopia: A Cross Sectional Study

Abstract: Abstract:Background: Globally, sexually transmitted diseases (STDs) remain a significant public health problem especially among young women. In Ethiopia, the prevalence of STDs among femal youths aged 15-24 years old continues to be a problem of young population. However, the factors associated with this problem is poorly studied. Thus, the purpose of this study is to assess sexual behavior and prevalence of STDs and factors associated among young women attending health facilities in Northern Ethiopia. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…In this study, students with poor knowledge of STIs were more likely to develop STIs than students with good knowledge. This finding agrees with those of other studies conducted in Mekelle [25], Wolaita Sodo University [27], and Bahir Dar town [33].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, students with poor knowledge of STIs were more likely to develop STIs than students with good knowledge. This finding agrees with those of other studies conducted in Mekelle [25], Wolaita Sodo University [27], and Bahir Dar town [33].…”
Section: Discussionsupporting
confidence: 93%
“…The finding is comparable with those of studies conducted on the University students in Wolaita Sodo (19.5%) [22] and Addis Ababa (15.74%) [23]. But, this finding was slightly lower than those of other studies conducted on Debre Birhan University students (28%) [24] and female youth at Mekelle (21.3%) [25]. The possible difference from Mekelle study might be due to the difference in the study area and study subjects were selected from the health facilities where there was a high probability of finding suspected cases.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In contrast, some studies have shown that there was no significant association between abortion and seropositivity of HBsAg among pregnant mothers [ 22 , 34 ]. Hepatitis B virus infection is sexually transmitted and the transmission increases with the duration of sexual activity and number of sexual partners [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies conducted among high school students at Bahir-dar and HIV patients in Ayder referral hospital, Northern Ethiopia reported that the prevalence of STIs is 13.1% and 8.5% reported to have syndromes of STIs respectively (Gebremichael H et al, 2017) (Gebrelibanos A et al, 2015). Study conducted among young women in Northern Ethiopia shows that self-reported prevalence of STIs in the last 12 months was 21.3% (Fisseha G AE, 2015). Surveillance conducted in Ethiopia in 8 health facilities located in Amhara, Oromia and Addis Ababa reported that commonest syndrome was vaginal discharge 50%, urethral discharge 31%, genital ulcer/sores 9%, lower abdominal pain 7.3%, and two syndrome were present in few patients 3% (FMOH, 2015).…”
Section: Introductionmentioning
confidence: 73%